PLN Smart Grid Network Security Analysis Using Blockchain Methods in the Context of Cyber Security - Ahmad Affandi Rasyad Nasution; Hasibuan, Muhammad Siddik (Journal of Computer Science and Informatics Engineering, 2024)
Currently, electricity cannot be separated from everyday life. Nearly every task humans perform on a daily basis involves the use of electrically powered gadgets. It is common knowledge that the use of electrical energy continues to increase over time. Application of Blockchain Technology to Information Security Systems uses qualitative methodology, analyzing and researching various literature sources related to blockchain and information security systems. This approach will support the understanding and assessment of the integration of blockchain technology with information security systems. The results obtained in this research are. Smart networks (smart grids) are resilient to natural disasters and attacks. Smart Grid is not only resistant to physical attacks, but also resistant to cyber attacks. Most economic progress comes from complex systems such as smart grids. Solar panel users, for example, may overload the power grid with power surges from these sources. The application of blockchain technology to information security systems offers a number of significant advantages, including robust information security solutions, reliable data storage, guaranteed data integrity, user anonymity, and transparency in data and transactions. It is important to discuss how blockchain technology can be applied to improve user privacy and information security systems.